Basic Aspects of Blood Clotting: Thrombokinase and Cofactors in the Conversion of Prothrombin to Thrombin - Ferguson, J. H; Wilson Ennis, Ella Gray; Iatridis, P. G; White, Norma B (Thrombosis and Haemostasis, 1967)
A basic biomathematical analysis of quantitative clotting test data becomes highly significant in the light of a complex logic which indicates a possible accord with certain postulated biophysical principles. Rectilinear plots are obtainable with one or other of two methods of analyzing the clotting-time data for an experimental system in which prothrombin is converted into thrombin by thrombokinase in the presence of specified cofactors.Determinants of enzymic activity fit the postulate of Michaelis-Menten kinetics and the Lineweaver-Burk double-reciprocal rectilinear plot. This holds when the ∼ substrate variable is (a) thrombokinase (as precursor of the true prothrombin-convertor enzyme), (b) specific cation (Ca++, Sr++, or Ba++), and (c) factor V (AcG). The validated assays are particularly meaningful in the case of factor V, and suggest a new system of unit age (AcGact)- Tentative Km values are given for these “substrate” functions.Determinants of effective thrombin (activated prothrombin) quasi-activity are studied by rectilinear log-log plots of endpoint clotting-times against the factor variable, when this is (a) prothrombin, (b) prothromboplastic phospholipid (cephalin), but (c) factor V (AcG) only to a limited extent. The discussion explains how these findings accord with certain colloidal principles that modify a basic enzyme formula based on “the inverse law.”Evidence of complexing of both substrate and enzyme with certain factors is provided, especially by exploring effects of successive suboptimal additions. The following mechanisms could explain the facts: (a) prothrombin + phospholipid form a colloidal (micellar) substrate complex ; (b) the true activating enzyme is thrombokinase after specific activation by cation (Ca++, normally) ; (c) factor V plays a dual role (in (a) and (b)), thus acting after the manner of an amboceptor. These key reactions should be added to the current “cascade” concept of blood clotting.